The Oxford handbook of cuneiform culture. - Radner, Karen; Robson, Eleanor (Oxford Oxford university press, 2011)
"The cuneiform script, the writing system of ancient Mesopotamia, was witness to one of the world's oldest literate cultures. For over three millennia, it was the vehicle of communication from (at its greatest extent) Iran to the Mediterranean, Anatolia to Egypt. The Oxford Handbook of Cuneiform Culture examines the Ancient Middle East through the lens of cuneiform writing. The contributors, a mix of scholars from across the disciplines, explore, define, and to some extent look beyond the boundaries of the written word, using Mesopotamia's clay tablets and stone inscriptions not just as 'texts' but also as material artefacts that offer much additional information about their creators, readers, users and owners"--
Machine generated contents note: -- I. Materiality and literacies -- 1. Tablets as artefacts, scribes as artisans, Jonathan Taylor -- 2. Accounting in proto-cuneiform, Robert K. Englund -- 3. Numeracy and metrology, Gregory Chambon -- 4. Levels of literacy, Niek Veldhuis -- 5. Literacy and gender, Brigitte Lion -- II. Individuals and communities -- 6. The person in Mesopotamian thought, Benjamin R. Foster -- 7. The scribe of the Flood Story and his circle, Frans van Koppen -- 8. Feasts for the living, the dead, and the gods, Hagan Brunke -- 9. Cuneiform writing in Neo-Babylonian temple communities, Michael Jursa -- 10. Freedom in ancient Near Eastern societies, Eva von Dassow -- III. Experts and novices -- 11. Teacher-student relationships: two case studies, Yoram Cohen & Sivan Kedar -- 12. Patron and client: Zimri-Lim and Asqudum the diviner, Dominique Charpin -- 13. Learned, rich, famous and unhappy: Ur-Utu of Sippar, Michel Tanret -- 14. Music, the work of professionals, Nele Ziegler -- 15. The education of Neo-Assyrian princes, Silvie Zamazalova -- IV. Decisions -- 16. Judicial decision-making: judges and arbitrators, Sophie Demare-Lafont -- 17. Royal decision-making: kings, magnates and scholars, Karen Radner -- 18. Assyria at war: strategy and conduct, Andreas Fuchs -- 19. Manipulating the gods: lamenting in context, Anne Lohnert -- 20. Magic rituals: conceptualisation and performance, Daniel Schwemer -- V. Interpretations -- 21. Sheep and sky: systems of divinatory interpretation, Ulla Susanne Koch -- 22. Making sense of time: observational and theoretical calendars, John M. Steele -- 23. Letters as correspondence, letters as literature, Fabienne Huber Vulliet -- 24. Keeping company with men of learning: the king as scholar, Eckart Frahm -- 25. From street altar to palace: reading the built environment of urban Babylonia, Heather D. Baker -- VI. Making knowledge -- 26. The production and dissemination of scholarly knowledge, Eleanor Robson -- 27. Tablets of schools and scholars: a portrait of the Old Babylonian corpus, Steve Tinney -- 28. Adapting to new contexts: cuneiform in Anatolia, Mark Weeden -- 29. Observing and describing the world through divination and astronomy, Francesca Rochberg -- 30. Berossos between tradition and innovation, Geert De Breucker -- VII. Shaping tradition -- 31. Agriculture as civilization: sages, farmers, and barbarians, Frans Wiggermann -- 32. Sourcing, organising, and administering medicinal ingredients, Barbara Bock -- 33. Changing images of kingship in Sumerian literature, Nicole Brisch -- 34. The pious king: royal patronage of temples, Caroline Waerzeggers -- 35. Cuneiform culture's last guardians: the old urban notability of Hellenistic Uruk, Philippe Clancier.
Keywords: Assyriology; Cuneiform inscriptions; Cuneiform writing; Assyria -- Civilization; Iraq -- Civilization -- To 634.